2003
DOI: 10.1097/00002093-200301000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Driving Impairment in Alzheimer Disease: A Comparison of Self and Observer Reports Versus Driving Evaluation

Abstract: This study examined the relationship between driving behaviors and awareness of deficit in patients with Alzheimer's disease (AD). Fifteen mildly impaired AD patients and 15 healthy elderly controls with valid drivers' licenses were administered a series of questionnaires concerning daily functioning and driving performance, and all 30 subjects were evaluated on a standardized road test. Self-report and caregiver/informant responses were compared with determine levels of discrepancy in ratings, while compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
1
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 27 publications
3
61
1
8
Order By: Relevance
“…The reason underlying the poor association between caregiver and objective ratings is unclear and was not empirically tested in this study. A number of reasons have been put forth to explain reporter bias in caregivers, including the desire to avoid interpersonal conflict or to deemphasize the progression of the disease because of reliance on the driver for transportation (Wild & Cotrell, 2003). In a study of 80 older drivers, 33% stated that their independence would be affected if their spouse stopped driving, even though they were all licensed drivers (Classen et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason underlying the poor association between caregiver and objective ratings is unclear and was not empirically tested in this study. A number of reasons have been put forth to explain reporter bias in caregivers, including the desire to avoid interpersonal conflict or to deemphasize the progression of the disease because of reliance on the driver for transportation (Wild & Cotrell, 2003). In a study of 80 older drivers, 33% stated that their independence would be affected if their spouse stopped driving, even though they were all licensed drivers (Classen et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, self-report and caregiver report measures that clinicians can use in the office to identify driving errors and risky behaviors are desirable. Several studies have found limited utility for self-report measures in AD because affected people experience reduced insight into their own cognitive deficits and denial of their reduced driving performance Cotrell & Wild, 1999;Dobbs, 1997;Hunt, Morris, Edwards, & Wilson, 1993;O'Neill et al, 1992;Wild & Cotrell, 2003). Families and caregivers often rely on input from physicians to make the final decision about driving cessation.…”
mentioning
confidence: 99%
“…Gish, Decina, Lococo, & McKnight, 1998;Wild & Cotrell, 2003;Wilson & Smith, 1983) and associated with previous incidents of unsafe driving or on-road driving assessment outcome (e.g., Galski, Bruno, & Ehle, 1993;Mazer, Korner-Bitensky, & Sofer, 1998;McKnight & McKnight, 1999;Schanke & Sundet, 2000).…”
mentioning
confidence: 99%
“…Specifically, the results of two recent studies demonstrated that both AD patients and their informants might overestimate the patient's driving abilities before the on-road driving test [37,38]. There exists a discrepancy between AD patients' and informants' ratings of patient driving ability and actual performance as rated by a professional driving instructor on the standardized on-road driving test.…”
Section: Discussionmentioning
confidence: 99%